2016
DOI: 10.1016/j.ijid.2016.01.003
|View full text |Cite
|
Sign up to set email alerts
|

Haemorrhagic fever with renal syndrome: literature review and distribution analysis in China

Abstract: Hantaviruses infect their reservoir hosts and humans, but the infection only causes disease in humans. In Asia and Europe (the Old World), the hantaviruses usually cause haemorrhagic fever with renal syndrome (HFRS). This article summarizes the current understanding of hantavirus epidemiology, as well as the clinical manifestations, pathogenesis, renal pathology, diagnosis, treatment, and prevention of HFRS. Moreover, the spatiotemporal distribution of HFRS was analysed based on the latest data obtained from t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
62
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(63 citation statements)
references
References 51 publications
0
62
0
Order By: Relevance
“…Phylogenetic analysis shows that at least nine clades of HTNV and five clades of SEOV are prevalent in China Zou et al, 2016), including the Xinyi and Fugong viruses that have been recently reported in specific epidemic foci (Ge et al, 2016;Gu et al, 2016). Rodent-borne hantaviruses have also been detected in Lao PDR, Thailand (Thailand hantavirus, THAIV) and Cambodia (THAIV-like virus) (Blasdell et al, 2011;Pattamadilok et al, 2006).…”
Section: Pathogenic Hantaviruses and Their Reservoirsmentioning
confidence: 95%
See 1 more Smart Citation
“…Phylogenetic analysis shows that at least nine clades of HTNV and five clades of SEOV are prevalent in China Zou et al, 2016), including the Xinyi and Fugong viruses that have been recently reported in specific epidemic foci (Ge et al, 2016;Gu et al, 2016). Rodent-borne hantaviruses have also been detected in Lao PDR, Thailand (Thailand hantavirus, THAIV) and Cambodia (THAIV-like virus) (Blasdell et al, 2011;Pattamadilok et al, 2006).…”
Section: Pathogenic Hantaviruses and Their Reservoirsmentioning
confidence: 95%
“…In China, HFRS is classified as a class B notifiable disease (Zou et al, 2016) and is considered a severe public health challenge (Zhang WY et al, 2014;Jiang et al, 2016). HTNV and SEOV are the major causes of HFRS (Song, 1999;Zhang S et al, 2014).…”
Section: Asian-pacific Countriesmentioning
confidence: 99%
“…Currently, about 20,000-50,000 cases/year are reported in mainland China, which account for 90% of all reported cases worldwide [5,8,9]. The foci of HFRS often locates in rural areas, which constitute more than 70% of the total number of cases, because of poor housing conditions and abundant rodent hosts [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…HFRS is predominant in European and Asian region, whereas HPS is the main syndrome caused by Hantavirus in US. HFRS presents usually as a 5-stage disease (Figure 2), following a 2-4 week incubation period [16]. During the Prodromal Stage (3-5 days) the patient is febrile with concomitant constitutional flu-like symptoms (headache, malaise, myalgia, anorexia, eye pain), whereas haemorrhagic manifestations (subconjunctival haemorrhage, petechiae and mucous membrane injection) may coexist [2].…”
Section: Epidemiology Clinical Features and Disease Severity Of Hantmentioning
confidence: 99%
“…Patients during the subsequent Hypotensive stage (1-2 days) present clinical signs of hypovolemic shock (up to 21-28%), with concomitant gastrointestinal symptoms (abdominal pain, nausea, vomiting) or signs of acute abdominal pain [16]. The wide ranges of exhibited manifestations are not specific during this stage, with wide differential diagnosis, restraining the further diagnosis process.…”
Section: Epidemiology Clinical Features and Disease Severity Of Hantmentioning
confidence: 99%